Reductions in tobacco smoke pollution and increases in support for smoke-free public places following the implementation of comprehensive smoke-free workplace legislation in the Republic of Ireland: findings from the ITC Ireland/UK Survey. (5th June 2006) - Fong, G T; Hyland, A; Borland, R; Hammond, D; Hastings, G; McNeill, A; Anderson, S; Cummings, K M; Allwright, S; Mulcahy, M; Howell, F; Clancy, L; et al.
Abstract : Objective: To evaluate the psychosocial and behavioural impact of the first ever national level comprehensive workplace smoke-free law, implemented in Ireland in March 2004. Design: Quasi-experimental prospective cohort survey: parallel cohort telephone surveys of national representative samples of adult smokers in Ireland (n = 769) and the UK (n = 416), surveyed before the law (December 2003 to January 2004) and 8–9 months after the law (December 2004 to January 2005). Main outcome measures: Respondents' reports of smoking in key public venues, support for total bans in those key venues, and behavioural changes due to the law. Results: The Irish law led to dramatic declines in reported smoking in all venues, including workplaces (62% to 14%), restaurants (85% to 3%), and bars/pubs (98% to 5%). Support for total bans among Irish smokers increased in all venues, including workplaces (43% to 67%), restaurants (45% to 77%), and bars/pubs (13% to 46%). Overall, 83% of Irish smokers reported that the smoke-free law was a "good" or "very good" thing. The proportion of Irish homes with smoking bans also increased. Approximately 46% of Irish smokers reported that the law had made them more likely to quit. Among Irish smokers who had quit at post-legislation, 80% reported that the law had helped them quit and 88% reported that the law helped them stay quit. Conclusion: The Ireland smoke-free law stands as a positive example of how a population-level policy intervention can achieve its public health goals while achieving a high level of acceptance among smokers. These findings support initiatives in many countries toward implementing smoke-free legislation, particularly those who have ratified the Framework Convention on Tobacco Control, which calls for legislation to reduce tobacco smoke pollution.